Mortality and Cause of Death—A 30-Year Follow-Up of Substance Misusers in Sweden. (15th October 2018) - von Greiff, Ninive; Skogens, Lisa; Berlin, Marie; Bergmark, Anders
ABSTRACT: Background : This article presents a 30-year follow-up study of a cohort of 1163 substance misusers who were in inpatient treatment in the early 1980s. Data was originally collected in the Swedish Drug Addict Treatment Evaluation (SWEDATE). Objectives : The aim is to examine the overall mortality and identify causes of death in different groups based on self-reported most dominant substance misuse among those who have died during January 1984–December 2013. Methods : SWEDATE-data was linked to the National Cause of Death Register. Five mutually exclusive study groups were created based on self-reported most dominant substance misuse for the last 12 months before intake to treatment: Alcohol, Cannabis, Stimulants, Opiates, and Other. The Standardized Mortality Ratio (SMR) was calculated. Results : During the follow-up, 40% died. SMR is 10.3 for women and 11.7 for men. The study groups differed regarding SMR; 13.1 in the Alcohol group, 9.2 in the Cannabis group, 9.6 in the Stimulants group, 16.7 in the Opiates group and 10.8 in the Other group. Drug related death was the most common cause of death (28% only underlying, 19% both underlying and contributing) followed by alcohol related reasons (17% vs. 9%). Conclusions : Alcohol misuse among substance abusers might have a negative impact on mortality rates. Methodological changes in how drug related deaths is registered affects the interpretation of the statistics of cause of death. Further analysis on the relation between drug related cause of death and drug misuse related death is needed.